IMPLEMENTATION OF JOINT MILITARY EXERCISES BETWEEN THE TNI AD AND THE ARMIES OF ASEAN COUNTRIES TO COUNTER THE SOUTH CHINA SEA CONFLICT: IMPLEMENTASI LATIHAN MILITER BERSAMA TNI AD DENGAN AD NEGARA ASEAN GUNA MENGHADAPI KONFLIK LAUT CHINA SELATAN - M. Hazmi Qusween; Ferdinand Hasudungan Siagian; Samsul Bahari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the improvement of military training cooperation strategies between the Indonesian Army (TNI AD) and the armies of ASEAN countries in facing the conflict in the South China Sea, which is increasingly heating up due to territorial claims and strategic interests by several major countries. This cooperation is considered crucial to strengthen regional security stability through increased interoperability and coordination between militaries. This study uses a qualitative approach with a case study design, involving in-depth interviews, literature studies, and analysis of related documents. The main focus of the research includes factors that influence, conditions of joint training cooperation between the Indonesian Army and the armies of ASEAN countries and strategies to implement these influencing factors so as to improve the quality and quantity of joint training between the Indonesian Army and the armies of ASEAN countries. The results of the study show that strategic military cooperation between the Indonesian Army is supported by Indonesia's national defense policy and a number of international agreements. Increasing joint military training allows ASEAN countries to build joint preparedness to face threats in the South China Sea. This strategy also emphasizes the importance of multilateral exercises in the future to increase solidarity and collective response. In conclusion, the military training agreement between the Indonesian Army and the armies of ASEAN countries is a strategic step in creating strong regional security and facing challenges in the South China Sea. Recommendations to improve the quality of joint training between the Indonesian Army and the armies of ASEAN countries include increasing the frequency of joint training and coordination mechanisms between ASEAN military leaders through short-term, medium-term and long-term strategies